KLASIFIKASI TINGKAT PARTISIPASI PEMILU BERDASARKAN SEKTOR INDUSTRI MENGGUNAKAN ALGORITMA NAÏVE BAYES - Yusuf Raharja; Arif Senja Fitrani; Rohman Dijaya (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2024)
Elections represent the highest form of people's power and a democratic means to elect representatives and leaders. Public participation, influenced by demographics especially in the industrial sector, is a crucial indicator of an election's success. This research aims to classify the level of electoral participation in Pasuruan Regency based on demographic aspects, particularly in the industrial sector of Pasuruan Regency. The demographic dataset includes geography, population, industrial sector and other aspects at the village level sourced from the Pasuruan Regency Central Statistics Agency with a total of 80 attributes designated as predictor attributes and 2019 election recapitulation data on the level of community participation at the voting place specified as target attribute. The preprocessing steps include data cleaning, data transformation, data integration, attribute correlation, random dataset, forming two model datasets, and splitting the data with a 70:30 ratio. The method used in this research is the classification method with the Naïve Bayes algorithm. The results of the testing of model dataset 1 produced an accuracy of 61.8% and model dataset two produced an accuracy of 67.6%. The number of industries in Pasuruan Regency does not have a significant influence on the level of public participation in elections in Pasuruan Regency.